DRINKING WATER SUPPLY ISSUES: MODELLING AND INTEGRATED MANAGEMENT FOR FUTURE SUSTAINABILITY. THE CASE OF THE CITY OF GUELMA, NORTH-EAST ALGERIA - Bennacer Leila; Benmechiche M.; Boubguira S.; Hami M.; Nouar T. (International Journal of Innovative Technologies in Social Science, 2024)
The city of Guelma has experienced remarkable urban sprawl over the last few decades, with a continuous expansion of the urban area to accommodate a growing population. This phenomenon is particularly accentuated by a high demographic growth rate, which increases the pressure on infrastructure and basic services, especially drinking water supply, due to the increasing needs of households. The main objective of this study is to analyse the contribution of the WEAP model to the management of drinking water supply in the different sectors of the city of Guelma. This approach aims to ensure effective and sustainable planning of water resources to meet the growing needs of the population in each sector, while preserving this essential resource. The results show that water resources are limited, with projected consumption increasing from 6 million m³ in 2008 to around 47 million m³ in 2050, while the population is expected to reach almost 800,000 inhabitants. All scenarios show a water deficit, where demand exceeds supply. The study therefore emphasises the need for integrated water resource management to ensure sustainability. It uses hydrological and demographic data to guide supply decisions and aims to develop effective strategies to address the growing water challenges in the city of Guelma.